Bleach Solution Requirement for Hatching of Daphnia magna Resting Eggs - Retnaningdyah, Catur; Ebert, Dieter (Journal of Tropical Life Science, 2016)
Daphnia (water fleas) belong to the zooplankton group called Cladocerans have sexual reproduction when conditions less favorable that produce diapausing eggs are enclosed in the ephippium. Hatching ephippial eggs in the laboratory is important in ecological, toxicology, genetical, and evolutionary studies. This study aims to improve the current methods of egg hatching from ephippium. Each of 50 ephippium were treated together by placing them in a glass jar and adding 50 mL bleach solution (sodium hypochlorite). Concentrations of sodium hypochlorite used in this experiment were 0%, 0.5%, 1%, 2%, 4% and 8%. These concentration treatments were crossed with the following exposure times (1, 2, 4, 8, 16, and 32 minutes). Culturing was done in 80 mL of artificial Daphnia medium, incubated in constant light and temperatures 20Â°C for 25 days. There were two repetitions in this experiment that were run at the same time. Result of this experiment showed that pretreatment with 0.5-8% bleach solution significantly increases the yield of total hatch rate of Daphnia magna resting eggs by about 21% over unbleached control. However, there was no significant difference among the bleach treatments. Concentration of bleach solution 0.5%, 1% and 4% significantly accelerated the time period until the first hatching (first day hatching). Difference of exposure time (1 - 32 minutes) at each concentration treatments were not influence the yield of total hatch and the time period until first hatching.